2023
DOI: 10.1111/hel.12961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of a proton pump inhibitor on Helicobacter pylori stool antigen testing

Abstract: Background Some patients find it difficult to discontinue proton pump inhibitors (PPIs). Unlike the 13C‐urea breath test (UBT), the stool antigen test (SAT), particularly when domestically produced kits are used, may be less likely to yield false‐negative results. Methods This prospective study included a convenience series of 35 healthy Japanese subjects. Based on a statistical calculation, acceptable numbers of subjects were considered at least 21 and 11 with and without Helicobacter pylori (H. pylori) infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A BLEIA, although used less commonly than an EIA/ELISA, has been reported to have good sensitivity and specificity and is hardly affected by the presence of oral PPIs. Its main strength lies in its ability to accurately diagnose H. pylori (6,7). We hope that BLEIAs will be more widely used in the future to reduce the number of false-negative H. pylori stool antigen test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A BLEIA, although used less commonly than an EIA/ELISA, has been reported to have good sensitivity and specificity and is hardly affected by the presence of oral PPIs. Its main strength lies in its ability to accurately diagnose H. pylori (6,7). We hope that BLEIAs will be more widely used in the future to reduce the number of false-negative H. pylori stool antigen test results.…”
Section: Discussionmentioning
confidence: 99%
“…The BLEIA™ 'EIKEN' H. pylori antigen test (Eiken Chemical, Tokyo, Japan) is based on a bioluminescent enzyme immunoassay (BLEIA) and was developed to detect H. pylori antigens in feces with high sensitivity (5)(6)(7)(8). This method was reported to be largely unaffected by the oral administration of proton pump inhibitors (PPIs) (7), Despite its effectiveness, however, the BLEIA is not widely used because it requires the collection of stool samples in a dedicated stool collection container (BL-stool collection container or BL container, BL Sampling Bottle; Eiken Chemical). If the H. pylori stool antigen could be measured using a BLEIA in samples stored in an S container, which is widely used for fecal occult blood testing in colorectal cancer screening, the highly accurate BLEIA could then be more widely implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the BLEIA was reported to have better sensitivity than immuno-enzymatic and immunochromatographic methods in a comparative study of six commercially available products in Japan ( 15 ). Subsequently, Kajihara et al compared 3 commercially available products in Japan and reported that the BLEIA showed high diagnostic accuracy at 100% (35/35) and 97.1% (34/35) before and after proton pump inhibitor (PPI) use, respectively, and was not easily affected by PPI use ( 16 ). To date, the diagnostic accuracy of SAT has been reported to have 96-100% sensitivity/97-100% specificity, and 75-90% sensitivity/96-100% specificity before and after eradication, respectively ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine treatment outcomes to distinguish between successful eradication and recrudescence to prevent the risk of underdiagnosis of treatment failure. Noninvasive tests are recommended, such as UBT and SAT [8,152,[162][163][164][165]. Treatment outcomes should be performed not less than 4 weeks after the completion of eradication therapy.…”
Section: Wg 4: Treatmentmentioning
confidence: 99%